Compact MIMO antenna with optimized mutual coupling reduction using DGS. Issue 2 (April 2014) - Ibrahim, Ahmed A.; Abdalla, Mahmoud A.; Abdel-Rahman, Adel B.; Hamed, Hesham F. A.
<x content-type="archive" xml:space="preserve">Abstract</x> A design of low mutual coupling between two microstrip patch antennas for multi input multi output antenna is presented. The two antenna elements operate at 5.8 GHz for wireless applications. The reduction of mutual coupling between the antenna elements is achieved by using a defected ground structure (DGS). The DGS is inserted between the microstrip patch antenna elements to limit the surface waves between them. The separation between the edges of the two elements has been achieved to be only 0.058λ0. The analysis of the correlation coefficient, diversity gain and total active reflection coefficient is presented to validate the performance of the multiple-input–multiple-output (MIMO) antenna. The isolation of the proposed MIMO antenna is 28 dB at 5.8 GHz and the envelope correlation equals 0.003. Owing to these good performances each antenna can operate almost independently. A good agreement is achieved between the simulated and the measured results.